Co-occurrence of antibiotic and metal resistance genes revealed in complete genome collection - Li, Li-Guan; Xia, Yu; Zhang, Tong (The ISME Journal, 2017)
The high frequency of antibiotic resistance is a global public health concern. More seriously, widespread metal pressure in the environment may facilitate the proliferation of antibiotic resistance via coselection of antibiotic resistance genes (ARGs) and metal resistance genes (MRGs). Given the lack of comprehensive understanding of the ARG and MRG coselection, in this study both abundance relationship and genetic linkage between ARGs and MRGs were rigorously investigated by performing a genomic analysis of a large complete genome collection. Many more ARGs were enriched in human-associated bacteria compared with those subjected to less anthropogenic interference. The signatures of ARG and MRG co-occurrence were much more frequent and the distance linkages between ARGs and MRGs were much more intimate in human pathogens than those less human-associated bacteria. Moreover, the co-occurrence structures in the habitat divisions were significantly different, which could be attributed to their distinct gene transfer potentials. More exogenous ARGs and MRGs on the genomes of human pathogens indicated the importance of recent resistance acquisition in resistome development of human commensal flora. Overall, the study emphasizes the potential risk associated with ARG and MRG coselection of both environmental and medical relevance.